[Cu13S2CNnBu26(acetylide)4]+: A Two‐Electron Superatom. (26th October 2016) - Chakrahari, Kiran Kumarvarma; Liao, Jian‐Hong; Kahlal, Samia; Liu, Yu‐Chiao; Chiang, Ming‐Hsi; Saillard, Jean‐Yves; Liu, C. W.
Abstract: The first structurally characterized copper cluster with a Cu13 centered cuboctahedral arrangement, a model of the bulk copper fcc structure, was observed in [Cu13 (S2 CN n Bu2 )6 (C≡CR)4 ](PF6 ) (R=C(O)OMe, C6 H4 F) nanoclusters. Four of the eight triangular faces of the cuboctahedron are capped by acetylide groups in μ3 fashion, and each of the six square faces is bridged by a dithiolate ligand in μ2, μ2 fashion, which leads to a truncated tetrahedron of twelve sulfur atoms. DFT calculations are fully consistent with the description of these Cu13 clusters as two‐electron superatoms, that is, a [Cu13 ] 11+ core passivated by ten monoanionic ligands, with an a1 HOMO containing two 1S jellium electrons.